FAKTOR- RISIKO KEJADIAN PNEUMONIA PADA BALITA DI WILAYAH KERJA PUSKESMAS SIBERIDA KECAMATAN BATANG GANSAL TAHUN 2015 - Seri Asnawati Munthe (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2016)
Good housing is composed of a collection of houses that are equipped with numerous amenities such as a means of supporting roads, channels dirty water, trash, clean source of water, and close to the Centre of public health. Residential location should be free of flooding according to the standard public housing architecture. Essentially intended to provide a reasonably good home living in the form of design, layout and spacious room and other facilities in order to meet the needs of a family or can meet the requirements of home living a healthy and fun. Home or a bad place to live (slums) can support the occurrence of transmission of diseases and health problems, including pneumonia, Acute Respiratory tract infections (RESPIRATORY) remains an important health issue, because they caused the deaths of babies and toddlers. In case of discovery of Indragiri Hulu Regency of RESPIRATORY 2013 is the first rank of the 10 biggest disease, as many as 35.339 cases (34,09%), followed by as many as 10.981 gastritis disease cases (10,59%). This disease from year to year is always the first, caused by environmental conditions, where almost every year of Indragiri Hulu Regency got a flood and smoke that affect the respiratory tract and other causes. Pneumonia in Indragiri Hulu Regency in 2015 found as many as 220 cases amounted to 6.1%, we can see in the table below with a case of pneumonia in the Indragiri Hulu Regency:for that researchers want to find out to find out the risk factor for the occurrence of Pneumonia on Toddlers in the working area Clinics Batang Gansal Siberida 2015. With regard to this type of research is observational studies are retrospective (observations) with the design of the case case control. The overall population is a subject or object that will be examined, in this research is children aged under 59 months (toddler) 119 people. After analyzed results obtained the value of the P value of ventilation and OR 0.9, P value = 0.000 P humidity value = 0.000 fuel and OR 15,867, P value insect repellent and OR 0.667 valu memerokok, P = 0.000 and OR 2,240, P value behavior and OR 277,5, meaning that all the variables influencing the incidence of pneumonia.